Oxidative Stress Does Not Influence Subjective Pain Sensation in Inflammatory Bowel Disease Patients - Anna Krystyna Zielińska; Maciej Sałaga; Paweł Siwiński; Marcin Włodarczyk; Adam Dziki; Jakub Fichna (MDPI AG, 2021)
Oxidative stress (OS) has been proposed as a significant causative and propagating factor in inflammatory bowel diseases (IBDs). Modulation of OS is possible through antioxidants and inhibition of oxidizing enzymes. Thirty-one IBD patients and thirty-two controls were included in the study. The aim was to examine the levels of OS in colonic tissue of IBD requiring surgical intervention and control group, and their association with pain intensity. Total antioxidant capacity (TAC), superoxide dismutase (SOD) and catalase (CAT) activity, glutathione (GSH) and oxidized glutathione (GSSG) levels, and glutathione peroxidase (GPX) activity as markers of antioxidant defense were determined. Cyclooxygenases activities (Total COX, COX-1 and COX-2) were measured as prooxidant enzymes. Thiobarbituric acid reactive substances (TBARS) concentrations were measured to evaluate lipid peroxidation. Disease activity was assessed, and each subject filled out VAS and Laitinen's pain assessment scales. Correlation between the OS, pain intensity, disease activity parameters, C-reactive protein (CRP), number of stools passed daily, disease duration, and dietary habits was investigated. No TAC differences were found between the groups. A significant decrease of SOD activity and GSH and GSSG levels was seen in IBD patients vs. controls, while GPX activity was diminished significantly only in CD patients. CAT and COX-1 activity was increased, and COX-2 significantly decreased in IBD. TBARS were significantly higher in CD patients compared to control group. No correlation was found between pain scores, inflammatory status, disease activity, disease duration, or dietary habits and OS markers. In our study, OS did not influence pain sensation reported by IBD patients.